2016
DOI: 10.3374/014.057.0103
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Fossil Record of Turtles of the CladePan-Chelydridae

Abstract: Turtles of the total clade Pan-Chelydridae have a relatively sparse fossil record that reaches back to the Late Cretaceous (Santonian). The clade was only present in North America during the Cretaceous but spread along unclear routes to Asia and Europe during the Paleocene, only to go extinct on those continents by the end of the Pliocene. Final dispersal to South America took place at some time during the late Neogene. The ecology of stem chelydrids seems to have been similar to that of the extant Chelydra se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Given that western North America was separated from eastern North America by the intercontinental seaway, it is possible that various taxa migrated to eastern North America via the Arctic [118]. The Bering Land Bridge was utilized by chelydrids and the Emys orbicularis -lineage to disperse to Eurasia during the Paleogene [119, 120] and Neogene [121], respectively (Fig. 11c).…”
Section: Resultsmentioning
confidence: 99%
“…Given that western North America was separated from eastern North America by the intercontinental seaway, it is possible that various taxa migrated to eastern North America via the Arctic [118]. The Bering Land Bridge was utilized by chelydrids and the Emys orbicularis -lineage to disperse to Eurasia during the Paleogene [119, 120] and Neogene [121], respectively (Fig. 11c).…”
Section: Resultsmentioning
confidence: 99%
“…Plastral scutes.-Testudinoids are unique among extant turtles by possessing paired gulars, humerals, pectorals, abdominals, femorals, and anals (Hutchison and Bramble, 1981), in contrast to extant chelydrids and kinosternoids, which possess intergulars, but lack pectorals (Joyce, 2016;Joyce and Bourque, 2016). A recent phylogenetic analysis of Americhelydia with focus on Chelydroidea (i.e., the clade consisting of Chelydridae and Kinosternoidea) concluded that the lack of pectorals is a synapomorphy of Chelydroidea, but that pectorals were secondarily reacquired within this clade, for instance in the Paleocene dermatemydid Agomphus pectoralis (Cope, 1868) (Lyson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This general pattern would not hold true if Cardichelyon rogerwoodi were a testudinoid because this turtle would have crossed the Behring Land Bridge long before the climatic event that allowed the coordinated dispersal of its relatives (Vlachos, 2018), as early as the Tiffanian (Hutchison, 2013). In contrast, if Cardichelyon rogerwoodi is a chelydroid, no uncoordinated dispersal event is needed to explain its presence in the Paleocene fossil record of North America because this clade was endemic to this continent for most of its history (Joyce, 2016;Joyce and Bourque, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…; Joyce et al . ; Joyce ). Although morphological evidence has subsequently been found to support some of the propositions of molecular studies (e.g.…”
Section: Independent Origins Of Marine Life In Turtlesmentioning
confidence: 99%